THE RESPONSIBILITY OF THE SIMALUNGUN REGENCY GOVERNMENT IN PROVIDING ELECTRICITY FOR EDUCATIONAL INSTITUTIONS AT SINAR BARU PUBLIC ELEMENTARY SCHOOL IN THE PERSPECTIVE OF SIYASAH DUSTURIYAH (REVIEW OF MINISTERIAL REGULATION OF EDUCATION AND CULTURE NUMBER - Fahmi Aulia Sinaga; Maulidya Mora Matondang (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to analyze the responsibility of the Simalungun Regency Government in providing electricity for SD Negeri Sinar Baru based on the perspective of siyasah syar‘iyyah and Minister of Education Regulation (Permendikbud) Number 22 of 2023. Using an empirical research approach, data were obtained through interviews, observations, and document studies on the school's condition, local policies, and technical barriers in the field. The findings reveal that SD Negeri Sinar Baru still lacks adequate electricity access due to geographical constraints, budget limitations, and logistical challenges. This condition negatively affects the quality of teaching and learning and contradicts the principles of hifẓ al-din, hifẓ al-‘aql, and hifẓ al-nasl in Maqasid al-Syari‘ah, as well as the obligations stipulated in Article 9 paragraph (2) point g of Permendikbud Number 22 of 2023. The study recommends budget prioritization, cross-sector synergy, and the utilization of renewable energy to accelerate electricity provision for remote schools.